2012
DOI: 10.1097/ypg.0b013e3283518586
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of PTPN5, the gene encoding the striatal-enriched protein tyrosine phosphatase, in schizophrenia and cognition

Abstract: Objective STriatal-Enriched protein tyrosine Phosphatase (STEP) is a brain-specific member of the PTP family that has been implicated in learning and memory. In this study, we examined the association of the PTPN5 (protein-tyrosine-phosphatase non-receptor 5) gene, which encodes for STEP, with both schizophrenia and cognitive functioning in the Israeli Jewish population. Methods A 868 subjects schizophrenia (SZ) case-control study was performed (286 cases and 582 controls). Eleven STEP tagging SNPs were sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 73 publications
(83 reference statements)
0
9
0
Order By: Relevance
“…STEP KO mice were less likely to experience cognitive impairments following subchronic administration of PCP (Carty et al, 2012). Haplotype analysis has found a nominal association between the single nucleotide polymorphism (SNP) rs4075664 of PTPN5 and schizophrenia in an Israeli population sample (Pelov et al, 2012), with three SNPs displaying a stronger association with schizophrenia in males: rs4075664, rs2278732, and rs4757710 (Pelov et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…STEP KO mice were less likely to experience cognitive impairments following subchronic administration of PCP (Carty et al, 2012). Haplotype analysis has found a nominal association between the single nucleotide polymorphism (SNP) rs4075664 of PTPN5 and schizophrenia in an Israeli population sample (Pelov et al, 2012), with three SNPs displaying a stronger association with schizophrenia in males: rs4075664, rs2278732, and rs4757710 (Pelov et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…STEP KO mice are resistant to the locomotor, and cognitive effects of psychotomimetics and neuroleptic treatment of mice result in STEP 61 inactivation [2]. Moreover, a case–control study found nominal association between PTPN5 SNP rs4075664 and SZ in all the samples examined and a significant association of two additional SNPs (rs2278732 and rs4757710) in male samples from an Israeli Jewish cohort [20]. These studies indicate that BDNF signaling is generally low, while STEP 61 signaling is generally high in SZ patients and in animal models of SZ.…”
Section: Introductionmentioning
confidence: 99%
“…Statistical analysis of the observed data shows that there was an association (P = 0.003) between patient's group and controls in terms of genotypes of single-nucleotide polymorphism 1 rather than single-nucleotide polymorphism 2 of neuregulin 1. (2011) [98] 868 Israeli Jewish participants, of whom 286 were patients with SZ and 582 were healthy controls. SZ patients were included with information regarding ethnicity (Ashkenazi vs. non-Ashkenazi origin).…”
Section: Naz Et Almentioning
confidence: 99%
“…The variants of protein tyrosine phosphatase non-receptor 5 (PTPN5), the STEP encoding gene involved in glutamate receptor trafficking, are associated with both the diagnosis of SCZ and with neurocognitive function in general [98].…”
Section: Genes Involved In Glutamatergic Pathwaymentioning
confidence: 99%